2017
DOI: 10.1177/2192568217706700
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Postoperative Pain Scores Predict Neck Pain Profile up to 1 Year Following Anterior Cervical Discectomy and Fusion

Abstract: Study Design:Retrospective cohort review.Objective:To assess whether immediate postoperative neck pain scores accurately predict 12-month visual analog scale–neck pain (VAS-NP) outcomes following Anterior Cervical Discectomy and Fusion surgery (ACDF).Methods:This was a retrospective study of 82 patients undergoing elective ACDF surgery at a major academic medical center. Patient reported outcomes measures VAS-NP scores were recorded on the first postoperative day, then at 6-weeks, 3, 6, and 12-months after sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The purpose of the current study was to determine the comparative PPV of cervical oblique MRI, which can thus help clinicians to predict prognosis after surgery, with a prospective view of pain. Adogwa et al 1) demonstrated that immediate postoperative pain score accurately predicts and correlates with 1-year pain score after an anterior cervical discectomy and fusion (ACDF) procedure. Thus, we hypothesized that patients who experienced immediate pain relief were diagnosed and treated appropriately based on MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the current study was to determine the comparative PPV of cervical oblique MRI, which can thus help clinicians to predict prognosis after surgery, with a prospective view of pain. Adogwa et al 1) demonstrated that immediate postoperative pain score accurately predicts and correlates with 1-year pain score after an anterior cervical discectomy and fusion (ACDF) procedure. Thus, we hypothesized that patients who experienced immediate pain relief were diagnosed and treated appropriately based on MRI findings.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior cervical discectomy and fusion (ACDF) is one of the most commonly performed procedures for patients suffering from a wide spectrum of cervical spine pathologies, 1 including degenerative disc disease, myelopathy, radiculopathy, trauma, and infection. 2 , 3 Advantages to the procedure include low postoperative complication rates, 4 consistent good results, and relative procedural ease, thereby making it a popular surgical strategy for patients with maladies of the cervical spine.…”
Section: Introductionmentioning
confidence: 99%